1997
DOI: 10.1093/bja/79.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Cardioventilatory coupling during anaesthesia

Abstract: In 20 spontaneously breathing patients undergoing minor surgical procedures under general anaesthesia, we examined the timing relationship of heart best and ventilation. Patients received propofol 2-2.5 mg kg-1 and fentanyl 1 microgram kg-1 and breathed a mixture of 1-1.5% isoflurane and 66% nitrous oxide in oxygen. We recorded ECG R wave times and the start of each inspiration. We observed that: (1) all subjects showed evidence of phase coupling in which heart beats occurred at constant phases of the ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 14 publications
6
60
1
Order By: Relevance
“…During anaesthesia, the RI _1 interval is the most consistent R wave-inspiratory timing relationship during cardioventilatory coupling (Galletly & Larsen, 1997b;Larsen et al 1999b). This is one reason why we believe it is generally the heart beat immediately preceding inspiration that triggers inspiratory onset.…”
Section: Figurementioning
confidence: 95%
“…During anaesthesia, the RI _1 interval is the most consistent R wave-inspiratory timing relationship during cardioventilatory coupling (Galletly & Larsen, 1997b;Larsen et al 1999b). This is one reason why we believe it is generally the heart beat immediately preceding inspiration that triggers inspiratory onset.…”
Section: Figurementioning
confidence: 95%
“…48 Cardioventilatory coupling (CVC) is another concept, which specifically refers to the influence of timing of breathing on cardiac activity. 17,19,47 CVC is quantified based on the temporary alignment between the R waves of the electrocardiogram (ECG) and inspiratory onsets, using the R-peak to inspiratory-onset interval plot. Galletly and Larsen showed that during anesthesia CVC places the heart beats and inspiratory onsets such that they are maximally affected by vagal modulation of RSA implying common physiological roles and significant relationship between CVC and RSA.…”
Section: Introductionmentioning
confidence: 99%
“…Although the functional role and precise physiological basis of cardio-respiratory interactions are still being revealed [13], it has been shown that this interaction changes between different states, such as during anaesthesia [14]. Phase-transition-like phenomena in synchronization have been shown to occur in rats as their depth of anaesthesia varies [9].…”
Section: Introductionmentioning
confidence: 99%